Probing the structure and dynamics of complex hydrocarbons with ionizing radiation from free-electron lasers - Borne, Kurtis (Kansas State University, 2024)
Directly imaging the ultrafast changes in molecules during photochemical reactions has been a long-standing goal for chemists and physicists. Over the past three decades, ultrafast and intense light sources, including free-electron lasers (FELs), have been developed. These tools have enabled measurements that can probe the structure and dynamics of photoexcited molecules with femtosecond time-resolution. As these light sources improved, photo and electron spectroscopies have likewise developed, enabling high-dimensional measurements that provide a wealth of information on light-matter interaction. In this thesis, FELs operating from the extreme ultraviolet (XUV) to the X-ray regime are used to study the electronic and structural properties of complex isolated molecules. Specifically, ultrafast electronic relaxation processes of the quadricyclane molecule are explored. This highly strained molecule and its isomer, norbornadiene, are photoswitches with promising candidacy for solar energy storage. Here we apply time-resolved photoelectron spectroscopy at a highly coherent XUV-FEL. The experimental results are combined with non-adiabatic molecular dynamic simulations. With the high photon energy XUV-FEL source, we are able to monitor the molecule from any electronic state involved in the photochemical reaction, and we observe two competing relaxation pathways. One pathway is distinguished by a coupling to several valence electronic states that return the system to the ground state within 100 femtoseconds. The other pathway involves slower motion along the long-lived Rydberg states. Both pathways facilitate isomerization with a predicted branching ratio of norbornadiene/quadricyclane at approximately 3:2 in the electronic ground state. Secondly, Coulomb explosion imaging (CEI) is discussed. This experimental technique applies coincidence momentum imaging of molecules that rapidly dissociate after being photoionized to a highly-charged state. This technique has generated a lot of excitement as it is a promising candidate for probing gas-phase molecular structures, with previous results showing a beautiful molecular frame picture. In this thesis, we apply this technique to isomers with different cyclic geometries, demonstrating that CEI can differentiate gas phase hydrocarbon isomers that contain no preferential X-ray absorption sites, nor unambiguous ways to define a molecular frame due to the absence of marker ion momenta. This work contributes to the understanding of ultrafast molecular dynamics that underlies several light-induced biological processes, and potential applications in the optical control of quantum molecular systems.
Keywords: Photoionization; Photoelectron spectroscopy; Coulomb explosion imaging; Femtochemistry